Anti-counterfeit education: examining the effectiveness of educational initiatives in deterring the demand of fashion counterfeit goods - Polfer, Kelby Lorraine (Kansas State University, 2013)
Within the global marketplace, the production and consumption of counterfeit goods represents a serious social problem. Scholars continue to suggest anti-counterfeit education as a means to resolve this global problem and curb the demand for counterfeit goods, but no scholarly research has empirically evaluated the effectiveness of anti-counterfeit education. Therefore, the purpose of this study is to draw upon such suggestions within the literature, and quantitatively assess the effectiveness of anti-counterfeit education on consumers' perceived knowledge, attitudes, and purchase intentions of fashion counterfeit goods. Convenience samples of male and female college students participated in this study. Utilizing a one-group pretest posttest, quasi-experimental design, the findings from a series of paired samples t-tests revealed a positive, significant change in consumers’ perceived knowledge of fashion counterfeit goods after viewing the anti-counterfeit educational unit. Negative, significant changes in consumers’ favorable attitudes and purchase intentions of fashion counterfeit goods were also revealed after the anti-counterfeit educational unit had been administered. Findings from this study provide relevant implications toward academicians, government officials, fashion retailers, and anti-counterfeiting organizations, such as how to develop effective anti-counterfeit educational content. Such parties with a vested interest in deterring the demand of fashion counterfeit goods should focus on formulating and implementing anti-counterfeit educational tools, such as campaigns and advertisements, which focus on the negative factors and consequences associated with the fashion counterfeit industry.
Keywords: Fashion counterfeit goods; Anti-counterfeit education; Fashion; Counterfeiting; Demand of counterfeit goods; Behavioral Sciences (0602)